Origen y evolución del neutro lo como marca de atributo - Herrero Ruiz de Loizaga, F. Javier (Revista de Filología Románica, 2002)
In modern Spanish, lo is a neuter form used as a substitute for the subjective complement after ser, estar and parecer, to avoid the repetition of a noun, adjective or adverb. Although in modern Spanish has become completely unusual, in old Spanish lo was sometimes used as a substitute for the subjective complement after pseudo-copulative verbs, specially after andar. The origin of this use seems to be in the latin utilization —in the beginning only sporadically— of neuter pronoun hoc to refer an elided subject complement, specially in cases in which the absence of that ponoun could lead to ambiguity about which element should be understood as elliptical: subject or subjective complement.